A close range baseband radar transceiver for application in borehole radar systems - Van der Merwe, P.J. (Paulus Jacobus) (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Electrical and Electronic Engineering)--University of Stellenbosch, 2007.